The Role of PHT1 Family Transporters in the Acquisition and Redistribution of Phosphorus in Plants - Victor Roch, Gurusunathan; Maharajan, Theivanayagam; Ceasar, Stanislaus Antony; Ignacimuthu, Savarimuthu (Critical reviews in plant sciences, 2019)
Phosphorus (P) is one of the most important macronutrients for plant growth and yield. Low availability of inorganic phosphate (Pi) in soil substantially curbs crop production, whereas excessive Pi fertilization causes economic and ecological problems. The rapid depletion of global rock phosphate (RP) reserves calls for efficient plant Pi-management. To cope with low Pi (LP) stress, plants have evolved morphological, physiological, molecular, and biochemical adaptations. Apart from arbuscular mycorrhizal fungi (AMF)-mediated Pi acquisition, Pi uptake, it's export, utilization, and remobilization depend on transport processes mediated by membrane bound PHosphate Transporters (PHTs), which are grouped into five families. Among these, the PHT1 family is the primary transporter involved in the acquisition of Pi from soil and redistribution within plants. In this review, we present a brief account on 5 PHTs (PHT1 to PHT5) and focus on PHT1s. We cover in detail the PHT1s identified and characterized until now in various plants including their phylogenetic relationships, induction by AMF, localization, and affinity. We also discuss the extant understanding of the regulation of PHT1s at transcriptional, post-transcriptional, and post-translational levels. Further exploitation of PHT1s will help overcome the problems associated with LP soils and assist in improving crop yields through sustainable agriculture.